Diels-alder cycloaddition of 2-azadienes to methyl 2-(2,6-dichlorophenyl)-2H-azirine-3-carboxylate in the synthesis of methyl 4-oxo-1,3-diazabicyclo[4.1.0]heptane-6-carboxylates - Alves, M. José (2004)
A number of fused 4-oxo-1,3-diazabicyclo[4.1.0]heptane-6-carboxylates, a new type of compound, have been obtained by Diels-Alder cycloaddition between nucleophilic 2-azadienes and an electrophilic 2H-azirine. The reactions are completely endo- and regioselective, the azirine being added by its less hindered face to the diene. There are two isomers 7 and 8 formed from dienes 1 due either to isomerization of the cycloadducts 7 and 8 or by isomerization of the C=N bond of the diene during the reaction. The isomer 10 is formed from diene 2e, and a single diastereoisomer structure 4a-i is formed from dienes 11. Some pyrimidones 8a,7c/8c, 7e, 10, 11d have been hydrolyzed leading to functionalised aziridines 12, 13 and 15.